Domesticating Property: Moral Economies of Post‐Socialist Homeownership Through Rental and Neighbour Relations - Olga Tkach (Social Inclusion)
This article analyses property relations in post‐socialism through the analytical lens of housing studies and moral economy, specifically in the context of rental and neighbour relations in urban apartment buildings. It draws on 50 in‐depth residential biographies of residents of St. Petersburg, Russia, collected between 2017 and 2021. The interviews represent a diversity of tenures, as well as direct and indirect voices of homeowners and non‐owners. The article begins by introducing the socio‐historical context of the privatisation and commodification of housing in post‐socialist Russia. Then, based on the stories of the origin of property and the intensity of attachment to it, I analyse owners’ homemaking through daily interactions with other owners and non‐owners who act as their tenants and neighbours. Focusing on privatised, mortgaged, and inherited residential property, I identify three trajectories of complex relationships between owners and non‐owners in urban buildings and modes of homemaking, at the intersection of monetary and non‐monetary relations and imaginaries of counterparts. I argue that despite everyday interactions in the housing market and in apartment blocks, both the owners of privatised Soviet property and new owner‐occupiers tend to avoid the total commercialisation of the home and to challenge the dominance of homeownership as the only socially sanctioned tenure.